FGFR2 Genetic Variant C.1019A > G p.(Tyr340Cys) in a Fetus with Pfeiffer Type II Syndrome Diagnosed by a Combination of 3D Ultrasound Phenotyping and DNA Sequencing - Scalia, Maria S.; Hezelgrave, Natasha L.; Cerdeira, A. Sofia; Tapon, Dagmar; Lees, Christopher C.; Cobben, Jan M. (Journal of Fetal Medicine, 2025)
A 38-year-old woman was referred at 20 weeks' gestation for multiple fetal anomalies detected on routine ultrasound screening. Initial findings included dolichocephaly, ventriculomegaly, craniofacial abnormalities, and limb anomalies, which led to the suspicion of a skeletal dysplasia. While microarray analysis was normal, rapid fetal exome sequencing identified a de novo pathogenic variant in the FGFR2 gene (c.1019A > G p.(Tyr340Cys)). Initially classified as a variant of uncertain significance due to initial ultrasound suspicion, targeted three and four dimensional ultrasound phenotyping revealed characteristic features of Pfeiffer syndrome type 2, including cloverleaf skull, proptosis, hypertelorism, broad thumbs and big toes, and radial-humeral synostosis. This case demonstrates the crucial interplay between advanced genetic testing and detailed ultrasound assessment in prenatal diagnosis. Accurate interpretation of genetic variants requires meticulous ultrasound phenotyping in a multidisciplinary setting, particularly for complex and rare conditions such as Pfeiffer syndrome type 2.
Keywords: Pfeiffer type II syndrome; prenatal phenotyping; prenatal exome sequencing; FGFR2 gene variant c.1019A > G p.(Tyr340Cys); three-dimensional ultrasound